Deskripsi Kemampuan Pemecahan Masalah Matematika Siswa Ditinjau dari Tipe Kepribadian Menurut Keirsey - Awi; Usman Mulbar; Sahriani (Issues in Mathematics Education (IMED), 2021)
This study aims to describe the student’s ability to solve mathematical problems with Polya's steps (understanding the problem, devising a plan, carrying out the plan and looking back,) viewed from personality types according to Keirsey. This research is descriptive-qualitative. The research subjects were 4 students from class XI of Senior High School, with one subject for each personality type. The research instrument uses personality type classification instruments, problem-solving tests, and interview guidelines. The results of the research showed that from each of the students with the type of Keirsey personality, in solve mathematical problems more tend to be on types of Guardian and Rational personalities, can do every step of Polya’s problem-solving. Next, are the Idealist and Artisan types which are still lacking at the steps certain solving the problem of the problems given.